(untitled) (Bangladesh Journal of Orthodontics and Dentofacial Orthopedics, 2018)
Crowding is a common presentation among thepatients seeking orthodontic treatment. The cause of crowding could be various such as mesiodistal tooth width discrepancy, boney discrepancy among the jaw, earlyloss of deciduous molar, different patterns of malocclusion, ethnic group, nutritional and developmental factor. Materials and Methods: One hundred cases were selected among which 31 were male and 69 were female, 70 cases had crowded dentition and 30 cases had non crowded dentition. Bolton’s Overall ratio and Anterior ratio were calculated for every case and comparison was done among crowded and non crowded dentitions. Result: Mean Overall ratio and mean anterior ratio were found to be 91.06% and 79.66% Neither Overall ratio nor Anterior ratio was significant for crowding and non crowding cases. On comparing for male and female, only anterior ratio was found to be significant in female in crowding and non crowding cases. Ban J Orthod & Dentofac Orthop, April 2014; Vol-4 (1-2), P.12-15